2023
DOI: 10.3389/fpsyt.2023.1097873
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, insomnia, stress, and the way of coping emotions as risk factors for ischemic stroke and their influence on stroke severity: A case–control study in Lebanon

Abstract: BackgroundStroke is a leading cause of disability and death worldwide. There are numerous debates regarding the relationship between depression, anxiety, insomnia, perceived stress, and ischemic stroke. Moreover, no research on the efficacy of emotion regulation, which is critical for various components of healthy affective and social adaptability, is being conducted. To the best of our knowledge, this is the first study in the MENA region to shed light on the relationship between these conditions and stroke r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…All the aforementioned studies have indicated the significant impact of Psychological Health on stroke risk, with poor Psychological Health status increasing the likelihood of ischemic stroke(22). Elevated mood swings have a strong correlation with stroke and ischemic stroke(58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the aforementioned studies have indicated the significant impact of Psychological Health on stroke risk, with poor Psychological Health status increasing the likelihood of ischemic stroke(22). Elevated mood swings have a strong correlation with stroke and ischemic stroke(58).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cardiovascular medicine specialists have suggested the incorporation of psychological health evaluations in CVH assessment (4). Common risk factors for CVD include depression, anxiety, insomnia, and stress (20)(21)(22). This indicates the complexity of psychological health and the challenge of measuring it accurately (4,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent study, people with emotional disturbances such as stress or depression are more likely to have strokes. Maalouf et al, 2023).…”
Section: The Relationship Between Health Anxiety Score and Socio-demo...mentioning
confidence: 99%
“…Between 25% and 50% of patients develop GAD (Generalized Anxiety Disorder) in the fi rst few months after stroke, with a small reduction in incidence over the next three years. Phobic disorders and GAD are the most common types of anxiety disorders after a stroke [60][61][62].…”
Section: Usa Revisionmentioning
confidence: 99%